The Adipofascial Lateral Intercostal Perforator Flap in Partial Breast Reconstruction - Joao Correia Anacleto, MD; Carlos Mavioso, MD; David Gomes Pinto, MD; Pedro Gouveia, PhD; Marcio Debiasi, MD; Ljuba Morando, MD; Maria Joao Cardoso, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. The lateral intercostal artery perforator flap, first described by Hamdi et al as a partial replacement technique for breast-conserving surgery (BCS), was traditionally a fasciocutaneous flap with the inherent skin scar on the lateral chest wall. Trying to limit donor site morbidity, we further modified the original lateral intercostal artery perforator flap, harvesting tissue on the same perforator without the skin paddle, the associated scar, and the need to reposition the patient on the operating table. Methods:. We retrospectively analyzed 52 patients who underwent partial breast replacement after BCS between 2015 and 2020. We compared the 27 patients with the adipofascial lateral intercostal perforator flap (ALIP) with the remaining 25 replacement flaps regarding postoperative complications and aesthetic outcomes. Results:. An increased number of postoperative seromas were detected in the ALIP group according to the Clavien-Dindo classification; however, most of them were minor and did not delay adjuvant treatments or compromise cosmetic results. The aesthetic outcome evaluated through the Web BCCT.core workstation 1 year after surgery was shown to be identical between both groups. Conclusions:. The ALIP represents an alternative flap for tissue replacement in BCS, achieving overall similar complication rates and identical aesthetic outcomes when compared with other local perforator flaps, with reduced skin scars.